Žižkovský činžák - Tomašovic, Marko; Marko Tomašovic (České vysoké učení technické v Praze, 2019)
Dostavba bloku na Žižkově s řešením uličního průčelí.

Completion of the block in Zizkov with the main solving of the street facade.
Apartment House Žižkov
Keywords: bytovka; polyfunkce; dostavba; blok; Žižkov; residential building; multifunctional; completion; block; Zizkov